In vitro antioxidant and antiproliferative activities of methanolic plant part extracts of Theobroma cacao - Baharum, Zainal; Md. Akim, Abdah; Yap, Taufiq Yun Hin; Abd Hamid @ Abdul Razak, Roslida; Kasran, Rosmin (MDPI, 2014)
The aims of this study were to determine the antioxidant and antiproliferative activity of the following Theobroma cacao plant part methanolic extracts: leaf, bark, husk, fermented and unfermented shell, pith, root, and cherelle. Antioxidant activity was determined using 2,2-diphenyl-2-picrylhydrazyl (DPPH), thiobarbituric acid-reactive substances (TBARS), and Folin-Ciocalteu assays; the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium (MTT) assay was used to determine antiproliferative activity. The root extract had the highest antioxidant activity; its median effective dose (EC50) was 358.3 ± 7.0 µg/mL and total phenolic content was 22.0 ± 1.1 g GAE/100 g extract as compared to the other methanolic plant part extracts. Only the cherelle extract demonstrated 10.4% ± 1.1% inhibition activity in the lipid peroxidation assay. The MTT assay revealed that the leaf extract had the highest antiproliferative activity against MCF-7 cells [median inhibitory concentration (IC50) = 41.4 ± 3.3 µg/mL]. Given the overall high IC50 for the normal liver cell line WRL-68, this study indicates that T. cacao methanolic extracts have a cytotoxic effect in cancer cells, but not in normal cells. Planned future investigations will involve the purification, identification, determination of the mechanisms of action, and molecular assay of T. cacao plant extracts.